Upaya Guru Dalam Meningkatkan Motivasi Belajar Siswa Pada Masa Adaptasi Kebiasaan Baru - Bayu Widiyanto; Muhammad Abdul Halim Sidiq; Ervin Saifuddin Zuhri (ZAHRA: Research and Tought Elementary School of Islam Journal, 2022)
The New Habit Adaptation Period (IMR) or also known as the pandemic period is a period of new lifestyles that must pay attention to health protocols. MI Al-Azhar Senduro at AKB applies a blended learning model where the application is carried out alternately every day. However, many obstacles were encountered in its implementation. For example, limited time, students who are less enthusiastic when participating in learning, joking, not doing assignments, and also low student learning outcomes. This study used qualitative research methods. Data obtained by using observation, interviews and documentation. The target of this research is the fourth grade teacher at MI Al-Azhar Senduro. Efforts made by teachers in increasing students' learning motivation during the Covid-19 New Habit Adaptation (AKB) period by preparing for learning well and maximally, using interesting and varied learning methods and media, providing individual and classical motivation or advice, giving assignments with a competition system, carrying out daily tests, giving grades, giving punishment, giving rewards and finally reporting the results of the progress of students at school to parents.